2022
DOI: 10.1002/app.53481
|View full text |Cite
|
Sign up to set email alerts
|

A method for the treatment of black tea waste: Converting it into liquid mulching film and solid mulching film

Abstract: This work was aim to prepare biodegradable mulching film from biomass materials to reduce the environmental pollution caused by plastics. Black tea waste was divided into two parts and combined with degradable materials such as polyvinyl alcohol and cellulose to prepare two degradable mulching films: liquid mulching film (LMF) and solid mulching film (SMF). The optimum formula was developed after studying the effects of various components of degradable mulching film on mechanical properties in both dry and wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…W. Sun et al (2022) studied the production of biodegradable mulching film from biomass materials to reduce environmental pollution caused by plastic. Thus, the results of the study indicate that the liquid mulch film and solid mulch film showed high mechanical properties, UV resistance, water resistance, ageing resistance and biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…W. Sun et al (2022) studied the production of biodegradable mulching film from biomass materials to reduce environmental pollution caused by plastic. Thus, the results of the study indicate that the liquid mulch film and solid mulch film showed high mechanical properties, UV resistance, water resistance, ageing resistance and biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the many constitutive soil models available in LS‐DYNA, the elastoplastic soil model was chosen, as well as the 147 material MAT_FHWA_SOIL. The Drucker‐Prager yield criterion was added to the Mohr‐Coulomb yield criterion because it describes the soil behavior more realistically and avoids the singularity of the Mohr‐Coulomb yield criterion from affecting the convergence (Sun., 2014). The unmodified or standard Mohr‐Coulomb yield criterion is described by Equation () (Guo et al., 2006): Fbadbreak=Psinnormalϕgoodbreak+K()αJ2goodbreak−Ccosnormalϕgoodbreak=0$$\begin{equation} F=-P\sin \phi +K\left(\alpha \right)\sqrt{{J}_{2}}-C\cos \phi =0 \end{equation}$$where P is pressure in Pascal, ϕ is soil internal‐friction angle in radians, J 2 is the second invariant of skew part of the stress tensor, F is yield surface force, K ( α ) is tensor plane function angle, and C is the soil cohesion.…”
Section: Methodsmentioning
confidence: 99%
“…The compression failure of potato young stems can be roughly divided into the approximate elastic stage, yield stage, and deformation failure stage. It is difficult to measure the Poisson's ratio of potato stems because of their small size, high moisture content, and because they cannot reach the yield stage when unearthed (Sun, 2014). For the potato young stems, the same linear elastic material model MAT_ELASTIC has been adopted, with the numerical parameters as shown in Table 3 (Sun, 2014; Lai et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations